Optimization of Extrusion Parameters for Pearl Millet-Soy Noodles. - RUDRA, OM; RUDRA, SHALINI GAUR; SAGAR, VIDYA RAM; VENKATESH, ARUN KUMAR THIRUMANI (Current Research in Nutrition & Food Science, 2025)
Noodle is one of the wheat-based pasta, encompassing variants such as macaroni, spaghetti, and vermicelli. Pearl millet (Pennisetum glaucum) noodle is alternative to wheat with enhanced nutrition and offers gluten free alternative to wheat noodles with low glycemic index. It exhibited inadequate structural integrity with high solid loss and reduced water absorption capacity. Their cooking and textural quality were improved through substituting 50% pearl millet flour with defatted soy flour. It was produced through flour mix subjected to extrusion followed by drying for safe storage, cooling at ambient condition, packaging and storage. Following Central Comosite Rotatable Design, optimum condition was obtained as 71°C barrel temperature, 34.4% moisture content and 178rpm screw speed of extrusion processing. The solid loss, hydration capacity, cooking time and density were determined at optimized level of extrusion processing conditions. Their respective values were 12.5%, 1.84g/g, 240sec and 1155kg/m³ with desirability of 0.70. The gluten free noodles can be promoted to upgrade the nutritional content of popular snacks amongst youth and children.